2009
DOI: 10.1016/j.seizure.2009.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Toward a definition of MEG spike: Parametric description of spikes recorded simultaneously by MEG and depth electrodes

Abstract: There is not yet a formal definition of magnetoencephalography (MEG) spike. This study provides a parametric description and definition of clear-cut MEG spikes recorded simultaneously by MEG and depth electrodes (iEEG). A total number of 367 simultaneous MEG/iEEG spikes were selected for analysis. Distribution of morphologic spike parameters and detailed quantitative analysis of the basic morphologic characteristics of MEG spikes is provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 17 publications
2
15
0
Order By: Relevance
“…MEG/EEG recordings were manually inspected by experienced evaluators for the occurrence of epileptic spikes according to the criteria of the International Federation of Clinical Neurophysiology, taking special characteristics of MEG spikes into account. 12,13 All recorded epileptic MEG spikes and their EEG correlates were averaged in each patient. Moving equivalent current dipoles (moving ECD) were calculated from averaged MEG spikes using a single sphere head model.…”
Section: Magnetoencephalgraphy/electroencephalgraphy (Meg/eeg) Data Acquisition and Source Localisationmentioning
confidence: 99%
“…MEG/EEG recordings were manually inspected by experienced evaluators for the occurrence of epileptic spikes according to the criteria of the International Federation of Clinical Neurophysiology, taking special characteristics of MEG spikes into account. 12,13 All recorded epileptic MEG spikes and their EEG correlates were averaged in each patient. Moving equivalent current dipoles (moving ECD) were calculated from averaged MEG spikes using a single sphere head model.…”
Section: Magnetoencephalgraphy/electroencephalgraphy (Meg/eeg) Data Acquisition and Source Localisationmentioning
confidence: 99%
“…Epileptic MEG spikes were chosen according to the characteristics used for EEG. 20,21 For this study, clinical reports of MEG findings were used to avoid interpretational bias.…”
Section: M/eeg Proceduresmentioning
confidence: 99%
“…The spike shape, in particular its late slow wave part, has been proposed to have an impact on the sign of the hemodynamic response . Generally, the spike shapes recorded in different sessions can show considerable variations (Nowak et al 2009;Fernandez et al 2005) which may affect the corresponding BOLD responses. For example, Salek-Haddadi et al (2006) showed that including additional information about the duration of interictal discharges led to increased sensitivity in analyzing combined EEG-fMRI recordings.…”
Section: Introductionmentioning
confidence: 99%